The Content Analysis of Bisphenol A (BPA) on Water in Plastic Glass with Varying Temperatures and Contact Times using UV-VIS Spectrophotometer - Nugroho, Bayu; Pramudya, Yudhiakto; Widodo, Widodo (Universitas Ahmad Dahlan, 2018)
This study aims to analyze the content of Bisphenol A (BPA) on various temperatureandcontact timesbetween the plastic bag and water. For analysis of BPA, a sample made with variations of temperature (± 70°C, ± 80°C, ± 90°C) and contacttime(5 minutes, 10 minutes, 15 minutes) usingnine samples. To determine the concentration of BPA, Lambert-Beer law was employed.According to the analysis of data, the content of BPA on the temperature variation showed that the higher the temperature of the sample, the higher the content of Bisphenol A in the sample. The content of BPA with a variation of contact times stated that with the longer contact time, the higher the content of BPA.